Excitation Energy Transfer from Rhodamine 6G to Photochromic Fulgide - Sharaf Jassas1, Rabab; Abdullah El-Daly1, Samy; M. Asiri1, Abdullah; A Khan1, Salman (Asian Journal of Chemistry, 2014)
In this work, a new fluorescence photoswitching system consisting of fulgide as a photochrome and rhodamine 6G as a fluorophor was designed and studied in methanol, dichloromethane and dioxane. The spectra of both the closed form of fulgide and rhodamine 6G were overlapped. Since the fulgide exhibited non-fluorescence, the emission spectra of blended system were attributed to rhodamine 6G only. The intensity of the fluorescence emission spectra of the rhodamine 6G was modified by the photochromism of fulgide upon irradiation with UV light at different time in methanol, dichloromethane and dioxane. The blended system exhibited quenching in fluorescence emission spectra in different solvents.